A Clinical Insight into Progeria: New Drugs, New Hope? - Jorge Sales Marques (Medical Science: Recent Advances and Applications Vol. 1, 2025)
Introduction: Progeria is a rare autosomal dominant genetic disease characterized by premature aging in children. Also known as Hutchinson-Gilford syndrome, people suffering from it start showing several features such as very low weight, scleroderma, osteoporosis, and loss of hair within one year of age. Methods: A 5-month-old boy presented with hard skin since born and later showed nodules of different sizes with a lack of subcutaneous fat, associated with joint rigidity. Results: Skin biopsy reveals scleroderma form appearance. Exome study confirmed the diagnosis of progeria, with a positive PCNA gene. Discussion: In recent years, Lonafarmib has given hope to progeria patients, increasing the rate of weight gain and decreasing vascular stiffness, bone structure, and audiological status in some children. Under a clinical trial, a new drug called progerinin has the main objective of reducing the vascular rigidity in association with lonafarmib. This association is the big hope for patients suffering from progeria.